Vitalising the University Education of Librarians - Ranganathan, S. R. (Journal of Information and Knowledge, 1966)
Describes, with illustrations from experience, the perennial struggle between the young and the Old librarians and explains how the teachers of library science should bridge the gap. Refers to the deterioration in the standard of teaching caused by a sudden increase in the number of library schools and the neglect of the norms of education. Warns against impoverishing the content and lowering the standard of the B Lib Sc course under the influence of some outmoded practices in some other countries, without reference to the present needs of India, Shows how the method of teaching library science is influenced by the British-Indian Factory Method of education in liberal arts, instead of the method appropriate to professional education. Explains the scientific basis of the course-structure recommended by the UGC Committee and enumerates possible methods of teaching. Finally, suggests the evaluation of the teaching, by calling for an assessment by the trained librarians who are giving service, the readers who are the consumers of the service, and the employers of the librarians.